Analysis of load frequency control performance assessment criteria. - Gross, G.
This paper presents the development and application of an analytic framework for the formulation and evaluation of control performance criteria in load frequency control (LFC). The framework is constructed so as to explicitly represent the uncertainty in the measured variables in LFC and to use metrics that are meaningful for the structure of the problem. The framework makes effective use of probability and random processes concepts to develop rather general criteria for LFC performance assessment. In fact, the NERC criteria CPS1 and CPS2 are special cases of the criteria of the framework. The paper thus provides an analytic rationale for the NERC control performance criteria. Analysis of the CPS1 and CPS2 criteria shows that, under conditions that are typically in effect in North American interconnections, the two criteria are redundant. Consequently, there is good analytical basis for not requiring the application of CPS2 once CPS1 is satisfied. Numerical results with four interconnections are given to illustrate the analytic results. The framework is a powerful construct that may be used to construct new criteria for LFC performance assessment
Keywords: NERC criteria CPS1.; NERC criteria CPS2.; North American interconnections; Automatic generation control; Load frequency control; Performance assessment criteria; Probability; Random processes; Uncertainty